Przemiany fazowe wody i jej obieg w przyrodzie w strukturze wiedzy uczniów w szkole ponadgimnazjalnej - Bielecka, Jolanta (My University, 2011)
Pracę pisano na temat „Przemian fazowych i obiegu wody w przyrodzie”. Poznawanie przyrody rozwija pozytywny stosunek ucznia do zjawisk przyrodniczych, a jako obywateli świata, przyroda nie powinna ani ich przerażać, ani też przytłaczać. Zatem uczniowie powinni badać przyrodę i tłumaczyć zjawiska w niej zachodzące, bo jest to jedyna metoda do zrozumienia świata, w którym żyje każdy człowiek, a dostosowane do potrzeb przyszłych specjalistów. Celem tej pracy było zaproponowanie takich działań, które mogłyby ukazać, z jednej strony, stan wiedzy uczniów dotyczący „Przemian fazowych i obiegu wody w przyrodzie” w poszczególnych typach szkół średnich z drugiej zaś strony, stan naszego środowiska, szczególnie województwa zachodniopomorskiego. Określono nowe podejście do nauczanych treści i określono wykonalność prowadzonych badań. Zadaniem było sformułowanie praw, które przedstawiają ścisły związek między wprowadzonym nowym programem nauczania, opartym na „Podstawach programowych”, a typem szkoły, możliwościami i zdolnościami uczniów oraz między programem nauczania, a treściami podawanymi uczniom, opartymi głównie na doświadczeniach uczniowskich. Ważne było aby uczniowie, poprzez samodzielne poszukiwanie i odkrywanie, dochodzili do poznania praw przyrody, a nauczyciel do wyjaśnienia celu, do jakiego zmierza wprowadzenie autorskiego programu nauczania. Jednocześnie w pracy tej zawarte są wyniki badań autorki, diagnozujące stan wiedzy i umiejętności uczniów różnych typów klas oraz spostrzeżenia autorki przed wprowadzeniem programu autorskiego i po realizacji materiału dotyczącego „Przemian fazowych wody i jej obiegu w przyrodzie”. Bez znajomości zagadnień fizyki z działu Termodynamiki, na który szczególnie zwrócono uwagę, nie można też zrozumieć roli, jaką odgrywa woda w energetyce; również w energetyce jądrowej. Badania wiadomości uczniów potwierdzają konieczność uważnego wyboru podawanych treści nauczania oraz konieczność kładzenia nacisku na zagadnienia, które najlepiej odpowiadają typom szkół i zainteresowaniom uczniów. Niniejsza praca przedstawia problemy, z którymi spotkała się autorka i środki jakie przyjęła dla ich rozwiązania. Podaje dobrze zweryfikowany program nauczania, który został zbadany za pomocą metody statystycznej. Autorka podaje wyniki ilościowe z opisem doświadczeń, które zostały zaproponowane do prowadzenia przez uczniów i zawiera wyniki własnych badań pedagogicznych. Przedstawia w formie diagramów środki dydaktyczne dla nauczyciela.

The objective of the thesis was to propose such activities which could, on one hand, show the state of pupils’ knowledge on the phase transitions of water and its circulation in nature in some types of secondary schools for pupils studying in the terms 2002/2003 and 2003/2004. On the other, it was to show the state of the natural environment, especially in the West Pomeranian Region. Thanks to this thesis one could learn what knowledge students possess, what their interests are, what the teacher’s attention should be drawn to in particular. A new approach to what is being taught and the feasibility of the conducted research have been identified. The task was to frame laws that show strict relationship between the introduced new curriculum based on the „Programme Foundations” and the type of school, possibilities and capabilities of pupils; and between the curriculum and knowledge provided to pupils, based mainly on pupils’ experiences. Another aim was to justify the necessity of such an activity so as to achieve the best possible results in the teaching process. It was important that students through individual research and explorations would reach the aim of learning the laws of nature, and the teacher would explain the aims behind introducing the original programme. At the same time, the thesis has contained the results of the author’s research, diagnosing the state of knowledge and capabilities of pupils from different types of classes, her observations before introducing the original programme related to “phase transitions of water and its circulation in nature”, and afterwards. The assumed aim has been reached. As it is clear from analyzing the results of research, pupils of general lyceums (general and specialized classes) and technical secondary schools (years 2003/2004), show a great level of capabilities to integrate the contents of the programme, as well as a high level of interest in nature and experiments in physics. It is the physical experiments conducted by students themselves that helped them realize that phenomena related to phase transitions of water and its circulation in nature has a significant influence on all spheres of life on earth. It is thanks to water that plants, animals and people can live. Water is the best solvent of various chemical compounds, regardless of its state of matter; it is also a means of transport. That is why one should take good care of water and save it. Without the knowledge of issues related to physics from the thermodynamics branch, which is of major focus here, one cannot comprehend the role of water in the power industry or nuclear power. Before introducing the original thermodynamics section in the programme, one had tried to present students with the regularity of processes which ruled ‘phase transitions of water and its circulation in nature’. Carrying out research on pupils’ knowledge in the scope of ‘phase transitions of water and its circulation in nature’ confirm the necessity of careful selection of information given to students and putting emphasis on issues which best match types of schools and pupils’ interests. This thesis shows issues which the author encountered in her work and the means she adopted to solve them. She provides a well-verified teaching programme which has been analyzed with the statistical method. She also provides results in quantities, describes experiments which were proposed to students to carry out and presents the results of own pedagogical research.
Phase Transitions of Water and Its Circulation in Nature in the Structure of Students’ Knowledge at a Post-Gymnasium Level
Wydział Studiów Edukacyjnych: Zakład Pedeutologii; Zakład Fizyki
Keywords: Water circulation; Transitions; Knowledge; Students; Nature; Physics; Research